2015
DOI: 10.1016/j.semnephrol.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Lupus Nephritis: Clinical Implications

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease marked by the presence of pathogenic autoantibodies, immune dysregulation, and chronic inflammation that may lead to increased morbidity and early mortality from end-organ damage. Over half of all SLE patients will develop lupus nephritis. Genetic association studies have identified more than fifty polymorphisms that contribute to lupus nephritis pathogenesis, including genetic variants associated with altered programmed cell death (PCD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 125 publications
(179 reference statements)
0
31
0
3
Order By: Relevance
“…Such alterations are likely due to abnormalities in receptor-mediated proximal and distal signaling pathways [68], many of which are current targets for novel therapeutic approaches to dampen inflammation and target organ damage in SLE [69]. Additional, future studies will be required to determine if dysregulation of signaling pathways that leads to aberrant cellular activation and secretion of inflammatory mediators is due to genetic [23, 70], epigenetic [71], and/or environmental triggers, such as vitamin D deficiency [51] and/or immune dysregulation caused by latent Epstein-Barr viral infection [72, 73]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alterations are likely due to abnormalities in receptor-mediated proximal and distal signaling pathways [68], many of which are current targets for novel therapeutic approaches to dampen inflammation and target organ damage in SLE [69]. Additional, future studies will be required to determine if dysregulation of signaling pathways that leads to aberrant cellular activation and secretion of inflammatory mediators is due to genetic [23, 70], epigenetic [71], and/or environmental triggers, such as vitamin D deficiency [51] and/or immune dysregulation caused by latent Epstein-Barr viral infection [72, 73]. …”
Section: Discussionmentioning
confidence: 99%
“…The tumor necrosis factor (TNF) superfamily member B lymphocyte stimulator (BLyS), secreted in response to type I and type II IFNs [19, 20], further supports and propagates autoantibody production as a survival factor for self-reactive B-lymphocytes [21]. In addition to driving the production of pathogenic autoantibodies, these mediators also contribute to inflammation associated with SLE disease flare [22] and organ damage [23]. Although these mediators contribute to SLE disease activity, their role in preclinical autoimmunity and transition to clinical disease are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed discussion of the genetics and pathogenesis of LN is beyond the scope of this review, but can be found in Munroe and James (33). Here we will focus on recent findings that may be applicable to the clinical management of LN.…”
Section: Genetics and Pathogenesismentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) have identified more than 50 susceptibility loci that contribute to lupus pathogenesis, including genetic variants associated with the initial phase of innate immunity and the amplifying, adaptive phase of the immune response [6][7][8]. However, the role of single nucleotide polymorphisms (SNPs) in the genetic contribution to SLE still awaits extensive investigation.…”
Section: Introductionmentioning
confidence: 99%